Sub-domain analytical model for armature reaction field of permanent magnet vernier machine. Issue 2 (7th March 2016) - Oner, Y.; Zhu, Z.Q.; Wu, L. J.; Ge, X.
Abstract : Purpose: – An analytical sub-domain model is developed for predicting the armature magnetic field in permanent magnet vernier machine (PMVM) which has either non-overlapping or overlapping windings. The developed model accounts for tooth-tips and flux modulation pole slots (FMPs). The paper aims to discuss these issues. Design/methodology/approach: – It is obtained by solving Poisson's and Laplace's equations in polar coordinates for each sub-domain, i.e. air gap, slots, slot openings at tooth-tips and FMP slots. Armature reaction field distributions in slots, slot openings FMPs, air-gap and magnet region and winding inductances are obtained from the analytical method and compared by finite element analysis. Findings: – It is found that the developed model can be employed to accurately predict the armature field and winding inductance for any combination of slots/FMPs/permanent magnets. In addition, it is observed that the winding inductance is high which results in significant armature reaction and poor power factor in PMVM. Originality/value: – The main contributions include: first, accurate sub-domain model for PMVM is proposed for armature reaction which is not addressed in literature; second, the model accounts the interaction between FMP and slot; and finally, developed sub-domain model is also used for inductance calculation.